Are men from mars, women from venus? Examining gender differences of consumers towards mobile-wallet adoption during pandemic - Ahmad S. Ajina; Hafiz Muhammad Usama Javed; Saqib Ali; Ahmad M. A. Zamil (Cogent Business & Management, 2023)
The post-covid-19 era has witnessed the need for mobile-wallet app adoption due to non-physical transactions. Prior researchers have captured consumers' mobile-wallet adoption by involving facilitators or inhibitors. The detailed effect of facilitators and inhabitations in developing consumers' intention regarding mobile-wallet apps in a single model remain untapped in the marketing literature. The current study used two lenses: behavioral reasoning theory and gender schema theory, to investigate reasons for and against mobile-wallet adoption in Pakistan. For this purpose, two independent but relevant studies were performed. Study 1 involved respondents from the Punjab province, while study 2 mainly focused on the other three provinces of Pakistan, i.e., Sindh, Baluchistan and Khyber Pakhtunkhwa. PLS was used for SEM and Multigroup analysis. Study 1s results revealed that attitude significantly influences intention. Moreover, "reason for" and "reason against" significantly affect consumers' attitudes and intentions for mobile-wallet app adoption. Study 2 confirmed the results of study 1 and provided significant differences between males and females regarding mobile-wallet adoption. Such as, males have a more substantial influence on mobile-wallet apps' adoption than females.
Keywords: 650; Pakistan; behavioral reasoning theory; gender schema theory; Mobile-wallet